PDF of the sum of two dependent normal random variables

Let X N ( 0 , 1 ) X\sim \mathcal{N}(0,1) and W B e r n o u l l i ( 1 2 ) W\sim Bernoulli(\frac12) be an independent random variables.Define the random variable Y Y as a function of X X and W W .

Y = h ( X , W ) = { X, if W=0 -X,if W=1 Y=h(X,W)=\left\{ {\text{X, if W=0}\atop \text{-X,if W=1}} \right.

Find the PDF of Z = X + Y Z=X+Y .

In the options, δ ( ) \delta(\cdot) denotes the Dirac Delta function.

3 4 + 5 6 \frac34 +\frac56 2 3 δ ( z 2 ) + 5 6 2 π e z 2 2 \frac23 \delta({\frac{z}{2}})+\frac{5}{6\sqrt{2\pi}} e^{-\frac{z^2}{2}} 2 3 + 1 12 2 π e z 2 3 \frac23 +\frac {1}{12\sqrt{2\pi}} e^{-\frac{z^2}{3}} 3 4 + 2 11 2 π e z 2 \frac34 + \frac{2} {11\sqrt{2\pi}} e^{-z^2} 1 2 δ ( z ) + 1 4 2 π e z 2 8 \frac12 \delta({z}) + \frac{1}{4\sqrt{2\pi}}e^{-\frac{z^2}{8}}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Noe Blassel
May 29, 2019

Y = X 1 W = 0 X 1 W = 1 Y=X\mathbb{1}_{W=0}-X\mathbb{1}_{W=1} , so Z = X + Y = X + X 1 W = 0 X 1 W = 1 = X ( 1 + 1 W = 0 1 W = 1 ) Z=X+Y=X+X\mathbb{1}_{W=0}-X\mathbb{1}_{W=1}=X(1+\mathbb{1}_{W=0}-\mathbb{1}_{W=1}) . Since W Bernoulli ( 1 2 ) W\sim \operatorname{Bernoulli}{(\frac{1}{2})} , 1 = 1 W = 0 + 1 W = 1 1=\mathbb{1}_{W=0}+\mathbb{1}_{W=1} , hence Z = X ( 1 W = 0 + 1 W = 1 + 1 W = 0 1 W = 1 ) = 2 X 1 W = 0 = Φ ( X , W ) Z=X(\mathbb{1}_{W=0}+\mathbb{1}_{W=1}+\mathbb{1}_{W=0}-\mathbb{1}_{W=1})=2X\mathbb{1}_{W=0}=\Phi(X,W) , where Φ ( x , w ) = 2 x 1 w = 0 \Phi(x,w)=2x\mathbb{1}_{w=0} . Now, let Ψ : R R \Psi:\mathbb{R}\rightarrow \mathbb{R} be a suitably general (ie positive or bounded) measurable function. E [ Ψ ( Z ) ] = E [ Ψ Φ ( X , W ) ] \mathbb{E}[\Psi(Z)]=\mathbb{E}[\Psi\circ\Phi(X,W)] . Using the joint density of ( X , W ) (X,W) , given that X X and W W are independent, we compute this as E [ Ψ ( Z ) ] = R 2 Ψ Φ ( x , w ) 1 2 π e x 2 2 1 2 ( δ 0 ( w ) + δ 1 ( w ) ) d x d w \mathbb{E}[\Psi(Z)]=\iint_{\mathbb{R^2}}\Psi\circ\Phi(x,w)\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}\frac{1}{2}(\delta_{0}(w)+\delta_{1}(w))dxdw , where δ a \delta_{a} is the Dirac suppported at a a . So, E [ Ψ ( Z ) ] = R 2 Ψ ( 2 x 1 w = 0 ) 1 2 π e x 2 2 1 2 ( δ 0 ( w ) + δ 1 ( w ) ) d x d w \mathbb{E}[\Psi(Z)]=\iint_{\mathbb{R^2}}\Psi(2x\mathbb{1}_{w=0})\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}\frac{1}{2}(\delta_{0}(w)+\delta_{1}(w))dxdw = 1 2 ( R Ψ ( 2 x ) 1 2 π e x 2 2 d x + R Ψ ( 0 ) 1 2 π e x 2 2 d x ) =\frac{1}{2}(\int_{\mathbb{R}}\Psi(2x)\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}dx+\int_{\mathbb{R}}\Psi(0)\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}dx) = 1 2 ( R Ψ ( 2 x ) 1 2 π e x 2 2 d x + Ψ ( 0 ) ) =\frac{1}{2}(\int_{\mathbb{R}}\Psi(2x)\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}dx+\Psi(0)) , by integrating with respect to w w . Now we write Ψ ( 0 ) = R Ψ ( x ) δ 0 ( x ) d x \Psi(0)=\int_{\mathbb{R}}\Psi(x)\delta_{0}(x)dx and R Ψ ( 2 x ) 1 2 π e x 2 2 d x = R Ψ ( x ) 1 2 2 π e x 2 8 d x \int_{\mathbb{R}}\Psi(2x)\frac{1}{\sqrt{2\pi}}e^{-\frac{x^2}{2}}dx=\int_{\mathbb{R}}\Psi(x)\frac{1}{2\sqrt{2\pi}}e^{-\frac{x^2}{8}}dx by the change of variables 2 x x 2x\leftrightarrow x . Finally, summing these up, we obtain that E [ Ψ ( Z ) ] = 1 2 ( R Ψ ( x ) ( 1 2 2 π e x 2 8 + δ 0 ( x ) ) d x ) = R Ψ ( x ) ( 1 4 2 π e x 2 8 + 1 2 δ 0 ( x ) ) d x \mathbb{E}[\Psi(Z)]=\frac{1}{2}(\int_{\mathbb{R}}\Psi(x)(\frac{1}{2\sqrt{2\pi}}e^{-\frac{x^2}{8}}+\delta_{0}(x))dx)=\int_{\mathbb{R}}\Psi(x)(\frac{1}{4\sqrt{2\pi}}e^{-\frac{x^2}{8}} +\frac{1}{2}\delta_{0}(x))dx . Since Ψ \Psi was arbitrary, this shows that the PDF of Z Z , f Z f_{Z} , is given by the expression f Z ( z ) = 1 4 2 π e z 2 8 + 1 2 δ 0 ( z ) f_{Z}(z)=\frac{1}{4\sqrt{2\pi}}e^{-\frac{z^2}{8}} +\frac{1}{2}\delta_{0}(z) which was one of the choices, by reconciling the notations δ 0 ( z ) = δ z \delta_{0}(z)=\delta z

Note: since there is Dirac gymnastics involved, strictly speaking, f Z f_{Z} is not a PDF.

Winod Dhamnekar
May 30, 2019

Note that by symmetry of N ( 0 , 1 ) \mathcal{N}(0,1) around zero, X -X is also N ( 0 , 1 ) \mathcal{N}(0,1) . In particular, we can write

F Y ( y ) = P ( Y y ) F_Y(y)=P(Y\leq y)

= P ( Y y W = 0 ) P ( W = 0 ) + P ( Y y W = 1 ) P ( W = 1 ) =P(Y\leq y|W=0)P(W=0)+P(Y\leq y|W=1)P(W=1)

= 1 2 P ( X y W = 0 ) + 1 2 P ( X y W = 1 ) =\frac12P(X\leq y|W=0)+\frac12P(-X\leq y|W=1)

= 1 2 P ( X y ) + 1 2 P ( X y ) =\frac12 P(X\leq y)+\frac12P(-X\leq y) since X X and W W are independent.

= 1 2 Φ ( y ) + 1 2 Φ ( y ) =\frac12\Phi(y) +\frac12\Phi(y)

= Φ ( y ) =\Phi(y)

Thus Y N ( 0 , 1 ) Y\sim \mathcal{N}(0,1) . Now note that,

Z = X + Y = { 2X, with probability 0.5 0, with probability 0.5 Z=X+Y= \left \{ {\text{2X, with probability 0.5} \atop \text{0, with probability 0.5} }\right.

Thus Z Z is a mixed random variable and its PDF is given by

f Z ( z ) = 1 2 δ 0 ( z ) + 1 2 f_Z(z)=\frac12 \delta_0(z) +\frac12 (PDF of 2X at z)

f Z ( z ) = 1 2 δ 0 ( z ) + 1 2 f_Z(z)=\frac12 \delta_0(z) +\frac12 (PDF of a N(0,4) at z)

f Z ( z ) = 1 2 δ ( z ) + 1 4 2 π e z 2 8 f_Z(z)=\frac12 \delta(z) +\frac{1}{4\sqrt{2\pi}}e^{-\frac{z^2}{8}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...